The Effect of Soft Skills, Work Culture, and Service Quality in the Satisfaction Level of the Students of Anesthesia Specialist Study Program of Diponegoro University, Semarang - Dwijatmiko, Heru; Samsudi, Samsudi; Rustono, Rustono; RC, Achmad Rifai (Universitas Negeri Semarang, 2019)
The lecturer’s soft skill is a part of personality competencies which becomes one of the competencies that must be possessed by lecturers. Basically, success in achieving an educational goal very much depends on the individuals' ability to carry out their duties. The main objective of this study is to analyze the influence of lecturer’s soft skills, work culture, and service quality on the satisfaction level of the students in the anesthesia specialist study program of Diponegoro University (UNDIP) Semarang. The study population is students of the anesthesia specialist program; the determined sample was 120 students selected using random sampling. Data was drawn using a questionnaire; they were then analyzed using the SPSS and the Lisrel 8.54 programs. The results show that (1) the effect of lecturer’s soft skills on service quality was 62.41%, and on student satisfaction was 59.29%; (2) the influence of work culture on service quality was 40.96%, and on student satisfaction was 43.56%; (3) the effect of service quality on student satisfaction was 50.41%; (4) the influence of the lecturer’s soft skills and work culture altogether on service quality was 51%; (5) the influence of lecturer’s soft skills, work culture, and quality of service altogether on students’ satisfaction was 72%. So, the satisfaction of the PPD UNDIP Semarang students very much depends on the dynamics of the lecturer’s soft skills, work culture, and service quality provided by the university, especially the medical faculty.